Avaliação experimental e computacional da eficiência de separadores ciclônicos aplicados na coleta e concentração do minério de ferro proveniente de secagem convectiva - Aguiar, Joao Gabriel Amaral (Universidade Federal de São Carlos, 2023)
Iron is closely related to the development of a country, being a key element in the production of various goods for daily use. One of the fundamental stages in its processing is the moisture content control. In this sense, the convective drying of iron ore generates the dragging of part of the particulate material, making necessary its recovery. In addition, the chemical composition of the iron ore is also an important factor, mainly associated to the reduction stage in the blast furnaces, linked to steel production. Cyclones are gas-solid separation equipment whose principle of action is based on the centrifugal force generated by the gas flow, inducing larger particles to be collected in the underflow and releasing the gas through the overflow, containing a fraction of the lighter material. In this way, this study sought to evaluate the efficiency of different configurations of cyclonic separators, acting as classifiers, seeking to evaluate the ore collection as well as its composition variation. Experimental data from iron ore characterization, separation tests carried out in a pilot unit and cyclone performance models found in the literature were used to evaluate three cyclonic separators in nine operational conditions. In addition, CFD – Computational Fluid Dynamics – simulations were carried out to support the study. In this sense, simulations were carried out following the RANS methodology – Reynolds Average Navier-Stokes – coupling the RSM – Reynolds Stress Model – for the gaseous phase turbulence, together with the DPM – Discrete Phase Model – for insertion of the solid, being an Eulerian-Lagrangian formulation with extensive citation in the literature. Stationary simulations were performed using the Fluent software, belonging to the ANSYS Student 2022 R1 package. The results indicated good agreement of the dynamic parameters of the gaseous flow from CFD simulations and literature models. In addition, there was a certain degree of adhesion between the simulated collection efficiency results and those obtained through the correlations, indicating recovery of the material in the order of 90%, within the operational conditions evaluated, although with significant deviations of 14% to 44% in relation to experimental data. The effect of the inlet velocity and equipment geometry on the separator performance has been majorly proven. The mineral classification was also investigated through CFD, but with considerably deviations to the experimental results. In short, there was a strong tendency of iron ore recovery and a noticeable performance of the cyclones as classifying devices.
Experimental and computational evaluation of cyclonic separators's efficiency applied to the collection and concentration of iron ore from convective drying
Keywords: CFD; Ciclones; Classificação mineral; Eficiência de coleta; Minério de ferro; Secagem convectiva; CFD; Cyclones; Collection efficiency; Convective drying; Iron ore; Mineral classification; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA